Development of Student Learning Worksheet Based on Discovery Learning to Improve Understanding of Animal Life Cycle Concept - Wijianti, Wijianti; Wahidmurni, Wahidmurni (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The purpose of this research is to develop a Student Learning Worksheet (LKS) based on discovery learning to improve the understanding of the concept of animal life cycle material in Grade IV Madrasah Ibtidiyah students, including: describing product specifications, explaining the level of product attractiveness, and explaining the difference in the level of understanding of student concepts from those learn by using LKS and not using LKS. The subjects of the study were the fourth grade students of MI Sunan Ampel Pakis. The research procedure follows five stages of the ten stages developed by Borg and Gall in the framework of developing modules of the research and development method. The five stages are research and information collecting, planning, developing preliminary forms of product, preliminary field testing, and playing product revision. Logical feasibility analysis of media worksheets using validation of material experts, linguists, design experts and subject matter experts; the attractiveness of student worksheets was empirically analyzed using a closed questionnaire of student responses, and differences in the level of understanding were analyzed through the t test of the pre test results before using the media and the post test results after using the media in the experimental class and the control class. The results showed that the worksheets produced were feasible to use with the predicate of validation both in terms of design, language, and learning, as well as very good in terms of material; Student responses also show a very interesting predicate; the level of concept understanding of students who learn to use LKS is better than those who do not use LKS. This indicates that the worksheets developed can be used to be applied in the next research phase.